2016
DOI: 10.1097/qai.0000000000000845
|View full text |Cite
|
Sign up to set email alerts
|

CD4/CD8 Ratio Predicts Yellow Fever Vaccine-Induced Antibody Titers in Virologically Suppressed HIV-Infected Patients

Abstract: ART-treated HIV-infected individuals seem to have impaired and/or less durable responses to YFV than HIV-uninfected individuals, which were associated with lower CD4(+)/CD8(+) ratio, but not with CD4(+) T-cell count. These results supports the notion that low CD4(+)/CD8(+) ratio, a marker linked to persistent immune activation, is a better indicator of functional immune disturbance than CD4(+) T-cell count in patients with successful ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 51 publications
4
32
0
1
Order By: Relevance
“…In our study, despite the elevated CD4 T cell count and high proportion of ART-suppressed individuals, HIV status was still associated with lower persistence of YF-specific NAb titers following an apparently adequate initial immunogenicity. Our results are consistent with prior publications suggesting that HIV-infected subjects still present lower responses to vaccines [1, 6, 16]. In addition, while the START and TEMPRANO trials demonstrated that earlier ART initiation dramatically reduces the risk of infectious outcomes, there was still a substantial risk of infectious outcomes in the immediate ART arms [36, 37].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, despite the elevated CD4 T cell count and high proportion of ART-suppressed individuals, HIV status was still associated with lower persistence of YF-specific NAb titers following an apparently adequate initial immunogenicity. Our results are consistent with prior publications suggesting that HIV-infected subjects still present lower responses to vaccines [1, 6, 16]. In addition, while the START and TEMPRANO trials demonstrated that earlier ART initiation dramatically reduces the risk of infectious outcomes, there was still a substantial risk of infectious outcomes in the immediate ART arms [36, 37].…”
Section: Discussionsupporting
confidence: 92%
“…NAb titers against YF virus were measured by Plaque Reduction Neutralization Test (PRNT) performed at Virologic Technology Laboratory of Bio-Manguinhos (LATEV, FIOCRUZ, Rio de Janeiro) as previously described [16]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…121 If travel to an endemic area cannot be avoided, yellow fever vaccination can be considered in asymptomatic HIV-infected individuals with CD4 T-cell lymphocyte counts 200 cells/ mm 3 . 121 …”
Section: Yellow Fever Vaccinationmentioning
confidence: 99%